Harnessing Regulatory T Cells for the Treatment of Inflammatory Bowel Disease. Issue 6 (June 2015) - Geem, Duke; Harusato, Akihito; Flannigan, Kyle; Denning, Timothy L.
Abstract : Abstract: Regulatory CD4 + T (Treg ) cells are comprised of a heterogeneous population of cells that play a vital role in suppressing inflammation and maintaining immune tolerance. The immunoregulatory function of Treg cells is especially important in the intestine where the mucosa is exposed to a diverse array of foreign antigens—including those derived from food and commensal bacteria. Treg cells are enriched in the intestinal lamina propria and provide a crucial function in promoting tolerance to enteric antigens while modulating tissue inflammation. Correspondingly, Treg cell dysfunction is associated with a breakdown in intestinal tolerance and the induction of aberrant immune responses that may contribute to the pathogenesis of inflammatory bowel disease. This review will provide a brief overview of Treg cell biology with a focus on Foxp3 + Treg and type 1 regulatory (Tr1) cells and summarize the evidence for defective Treg cells in experimental and human inflammatory bowel disease. The potential application of Treg cells as a treatment for inflammatory bowel disease will also be discussed in the context of Treg infusion therapy and the in vivo induction/expansion of intestinal Treg cells. Abstract : Article first published online 19 March 2015.